Sediment detachment and transport processes associated with internal erosion of soil pipes. Issue 1 (3rd May 2017) - Wilson, Glenn V.; Wells, Robert; Kuhnle, Roger; Fox, Garey; Nieber, John
Abstract: Subsurface flow can be an important process in gully erosion through its impact on decreasing soil cohesion and erosion resistance as soil water content or pressure increases and more directly by the effects of seepage forces on particle detachment and piping. The development of perched water tables fosters lateral flow that can result in seepage at the surface and/or formation of soil pipes by internal erosion of preferential flow paths. Continued internal erosion of soil pipes can lead to gullies, dam and levee failures. However, the processes involved in particle and aggregate detachment from soil pipe walls and transport processes within soil pipes have not been well studied or documented. This paper reviews the limited research on sediment detachment and transport in macropores and soil pipes and applies the knowledge learned from the much more extensive studies conducted on streams and industrial pipes to hydrogeologic conditions of soil pipes. Knowledge gaps are identified and recommendations are made for future research on sediment detachment and transport in soil pipes. Copyright © 2017 John Wiley & Sons, Ltd.